2017
DOI: 10.1111/cbdd.12987
|View full text |Cite
|
Sign up to set email alerts
|

Reprofiling of full‐length phosphonated carbocyclic 2′‐oxa‐3′‐aza‐nucleosides toward antiproliferative agents: Synthesis, antiproliferative activity, and molecular docking study

Abstract: A series of phosphonated carbocyclic 2'-oxa-3'-aza-nucleosides were synthesized via 1,3 dipolar cycloaddition and evaluated for their in vitro antiproliferative activity against the growth of cancer cell lines (MCF-7, A2780, HCT116) and normal non-transformed fibroblast (MRC5) using MTT assay. Synthesized compounds exhibited antiproliferative activity in the micromolar range. Compounds 11b showed the highest activity against MCF-7 cells (IC of 0.2344 μm). Cell cycle analysis was performed for compound 11b on M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…Two strains of H. pylori the ATCC 26695 and H. pylori P12 were screened. Antibacterial activity of the eight compounds was evaluated by MTT assay as previously described in literature with some modifications Each of the two strains was cultured in heart infusion broth (BHI). Final working solution (optical density 0.2) was taken by diluting the bacterial stock suspension in BHI.…”
Section: Methodsmentioning
confidence: 99%
“…Two strains of H. pylori the ATCC 26695 and H. pylori P12 were screened. Antibacterial activity of the eight compounds was evaluated by MTT assay as previously described in literature with some modifications Each of the two strains was cultured in heart infusion broth (BHI). Final working solution (optical density 0.2) was taken by diluting the bacterial stock suspension in BHI.…”
Section: Methodsmentioning
confidence: 99%
“…Samples were held on ice and analysed by flow cytometry. Data analysis of DNA contents (PI bound to DNA) of 20000 events was carried out (Bkhaitan et al, 2017). …”
Section: Cell Cycle Analysismentioning
confidence: 99%
“…Among this class of compounds, spirochromanone is a well-recognized privileged structure that has been commonly found in a plenty of chemical compounds with diverse biological activities. These compounds exhibit significant biological activities such as anticancer (Atta et al, 2010;El-Desoky et al, 2013), antitubercular (Mujahid et al, 2013;Mujahid et al, 2015), antimicrobials (Feng et al, 2014), histamine-3 antagonists (Becknell et al, 2012), antiarrhythmic (Elliott et al, 1992), acetyl-CoA carboxylase (ACC) inhibitors (Shinde et al, 2009;Huang et al, 2015), stearoyl-CoA desaturase-1 (SCD)-1 inhibitors (Uto et al, 2010), histone deacetylase (HDAC) inhibitors (Varasi et al, 2011;Thaler et al, 2016), antimalarial (Roberts et al, 2016), growth hormone secretagogues (Yang et al, 1998) and δ opioid receptor agonists (Le Bourdonnec et al, 2008). Thaler et al have reported a series of spirochromanes and evaluated their activity against HDAC as a well-established anticancer target (Thaler et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…[8,11] The genes encoding these proteins are absent from the genomes of man and other mammals; normally, this nucleoside is present in human urine, and its concentration is increased in tumor-bearing patients. [21][22][23][24][25][26][27][28][29] In our research group, isoxazolidine replacement has also been employed for Ψ modification, leading to the development of the isoxazolidinyl-C-nucleosides 1-3 ( Figure 1). [13,14] The majority of nucleoside analogs consist of modifications of the natural substrates in the heterocyclic base and/or the sugar moiety.…”
Section: Introductionmentioning
confidence: 99%